Răspunsuri

2014-06-19T13:30:04+03:00
Folosesti formula : ( a+b)^{2} =  a^{2}+ 2ab +  b^{2}
Si rezulta :  (3x)^{2}+2*3x*2+ 2^{2} =4
 9x^{2} + 12x + 4 = 4
 9x^{2} + 12 = 0
deci e ecutatie de gradul 2.
a = 9 ; b = 12 ; c = 0
discriminantul ecuatiei delta ( notez cu D )
D=  b^{2}-2ac => D= 12^{2}-2*9*0=   12^{2}  = 144
x1 = \frac{-b+ \sqrt{D} }{2a} =>  \frac{-12+ \sqrt{144} }{18} =  \frac{-12+12}{18} =  \frac{0}{18} = 0
x2= \frac{-12- \sqrt{144} }{18} =  \frac{-12-12}{18} =  \frac{24}{18} = \frac{4}{3}

sa-mi spui daca-i corect :o3